Influence of the Initial Beach Profile on the Sediment Transport Processes During Post‐Storm Onshore Bar Migration. Issue 4 (7th April 2023) - Grossmann, Florian; Hurther, David; Sánchez‐Arcilla, Agustín; Alsina, José M.
Abstract: Onshore bar migration is a characteristic bar behavior during post‐storm beach recovery. The present large‐scale experiments, feature bichromatic wave groups over an initially steep (1:15), fully‐evolving beach. The same accretive wave condition is applied on two different post‐storm beach profiles featuring outer and inner bars. They are characterized by a larger (smaller) shoreline erosion and a larger (smaller) outer breaker bar located farther away from (closer to) the shoreline depending on the larger (smaller) energy of the storm condition. After a considerable post‐storm recovery time, similar equilibrium profiles are obtained, stressing the link between wave condition and equilibrium beach configuration. However, the evolution toward the equilibrium is different and depends on the initial morphological condition (post‐storm beach profile). After the larger storm, the morphological evolution is termed accretive merging (AM) and characterized by merging of the two bars (outer bar dissipation). After the smaller storm, the morphological evolution denoted as accretive non‐merging (AN) is characterized by onshore migration of the two bars with constant distance between them (bar maintenance). This study focuses on processes around the outer bar. During AN it features wave breaking, causing large suspended net offshore transport. AM, in contrast, mainly features bedload related to short wave asymmetries and low decomposed net transport rate magnitudes. High suspended net offshore transport occurs solely onshore of the outer bar trough. This causes filling of the bar trough and bar dissipation during migration. Additionally, processes around the outer bars are linked to accretion onshore of the bars and at the shoreline. Plain Language Summary: Nearshore sandbars are seabed features that protect coastal infrastructure behind many sandy beaches around the world. In response to waves they change in shape and distance to the beach, playing a key role in beach recovery after storms. To improve understanding of their onshore movement (migration), experiments were conducted which represented natural conditions in a controlled laboratory setting. In this context, the underwater transport of sand was measured. Application of the same recovery wave condition to two different post‐storm beach profiles resulted in two different types of bar onshore migration. After long experimental duration, both types evolved toward relatively similar beach profiles but the different ways of reaching them might have important practical consequences. In general, bar migration was governed by the interaction of onshore‐ and offshore‐transporting processes. They, in turn, were influenced by wave breaking. Bars, furthermore, cause wave breaking—closing the feedback loop. Ultimately, the different wave breaking locations, resulting from the shape of the post‐storm profiles, caused the different types of bar onshore migration during recovery. The present results provide crucial information for the development of mathematical models to forecast beach evolution and safeguard human interests in the coastal zone. Key Points: Accretive wave condition determines quasi‐equilibrium recovery beach profile irrespective of initial profiles Configuration of post‐storm profiles determines type of accretive morphological evolution toward the quasi‐equilibrium profile Outer bar maintenance associated with wave breaking over the bar while breaking farther onshore leads to outer bar dissipation